3(2x+8)=-35+41

Simple and best practice solution for 3(2x+8)=-35+41 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+8)=-35+41 equation:



3(2x+8)=-35+41
We move all terms to the left:
3(2x+8)-(-35+41)=0
We add all the numbers together, and all the variables
3(2x+8)-6=0
We multiply parentheses
6x+24-6=0
We add all the numbers together, and all the variables
6x+18=0
We move all terms containing x to the left, all other terms to the right
6x=-18
x=-18/6
x=-3

See similar equations:

| -5+6b=1+3b | | 30x/2-6x=6x/6-48/3 | | 6x+10=4x+9 | | -5=8-6m | | 5(x-1)+2(7-2x)=0 | | 3k-20=5k+20 | | A²+4a=0 | | -2x-5=−2x−5=x-17 | | 4x-10=2(3x+13) | | 7x+11=2(4x+6) | | -9(y-9)=3y-39 | | 5(4x+5)+4=7x-36 | | 9=5/6t | | 6x+1/4(4x+8)=12 | | 3(2x+1)=5x4 | | 18+11w+11=14w-19 | | x^2=143 | | -3=7+v/2 | | −42=2(4m−1) | | 5(n)=5n-7 | | 4f=8f-8 | | -11+2u=-3u+19 | | 5n^2-12n+1=0 | | 19x=5+18x | | -10-10+p=-5p+10 | | 4g=2g-15+g | | 14x-(6x-8)=56 | | 2x-6=|4x+1| | | 15-2x=3x-2(2x+6) | | -48+10x-14x=36 | | 5(a+4)=4(a-3 | | (5x+1)+86=90 |

Equations solver categories